2003
DOI: 10.1159/000075831
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Conscious Recollection, False Recognition and Delusional Misidentification in Patients with Schizophrenia

Abstract: Background: Recognition memory (RM) is impaired in patients with schizophrenia, as they rely largely on feelings of familiarity rather than conscious recollection. It has been suggested that this abnormality may reflect a breakdown in strategic memory processes involved in both encoding and retrieval. By studying 2 patients with false recognition (FR; patient C.T.) and delusional misidentification (DM; patient B.C.), and a group of psychotic control patients, we examined proposals that FR and DM exist on a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
(43 reference statements)
3
13
0
Order By: Relevance
“…These fi ndings are consistent with their preserved familiarity rates recorded for visual and olfactory RM [10,11] and in other remember/know studies of visual RM in schizophrenia [8,9] . Taken together, the behavioural profi le suggests a greater degree of preservation within the mediodorsal-prefrontal pathway which subserves familiarity-aware memory, relative to the extended hippocampal pathway.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These fi ndings are consistent with their preserved familiarity rates recorded for visual and olfactory RM [10,11] and in other remember/know studies of visual RM in schizophrenia [8,9] . Taken together, the behavioural profi le suggests a greater degree of preservation within the mediodorsal-prefrontal pathway which subserves familiarity-aware memory, relative to the extended hippocampal pathway.…”
Section: Discussionsupporting
confidence: 90%
“…These results are signifi cant on two counts: this is the fi rst study to report remember/know data for stimuli presented in the auditory domain. Secondly, these data, when considered alongside conscious recollection rates for visual and olfactory RM reported in the same schizophrenic cohort [10,11] , demonstrate that, at least for this group of patients, conscious recollection defi ciencies are not modality specifi c. These fi ndings support our fi rst prediction that the conscious recollection defi cits are more likely to arise from a central impairment. However, it cannot be claimed at this stage that this impairment stems from a breakdown in strategic memory processes, since measures of source monitoring and/or temporal ordering are not reported.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…There are in fact several reports suggesting face-processing impairments in Capgras patients [31] , as well as studies that indicate a generalized defi cit in all facial recognition tasks in schizophrenic patients [32][33][34][35][36][37][38] . Moreover, visual scan path research on schizophrenic patients has shown that patients with more pronounced positive symptoms, such as delusions, demonstrate a pattern of extensive scanning of faces, refl ecting probably the distraction of these patients by irrelevant stimulus information [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Among them are papers on the descriptive differentiation of clinical syndromes for the purpose of refi ned interpretation of pathogenesis and experimental data (e.g. Capgras Syndrome) [3] , an evaluation of the classifi cations of manuals and assessment instruments that are actually used in everyday clinical practice, such as the ICD-10 [4,5] , new assessment instruments for specifi c purposes, e.g. psychotherapy (in preparation: operational psychodyndamic diagnostics), or therapeutically relevant studies on the pathogenesis of psychopathological syndromes [6] .…”
mentioning
confidence: 99%